Ascent of money (Australia : Chimerica Media Ltd., 2008)
This programs reveals everything we need to know about money, why did money stop being metal and morph into paper?, why do people never learn that stock market bubbles always end in busts?. Also discover that it was Rothschild as much as Wellington who defeated Napoleon at Waterloo and why it's the adoption of Arab methematics that allowed Renaissance art and architecture to flourish
Ep. 1. Dreams of avarice (47 min.) -- ep. 2. Human bondage (48 min.) -- ep. 3. Blowing bubbles (48 min.) -- ep. 4. Risky business (48 min.) -- ep. 5. Safe as houses (48 min.) -- ep. 6. Chimerica (48 min.)
Title from container
Executive producer, Simon Berthon ; editor, Matt Platts Mills
Keywords: Finance -- History; Economic history; Economics -- History; Money -- History; International finance -- History